Evaluasi Pertumbuhan Empat Populasi Ikan Nila (Oreochromis niloticus) di Kolam Percobaan Cijeruk, Bogor - Rudhy Gustiano; Titin Kurniasih; Otong Zenal Arifin (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2005)
The objective of the present study was to obtain good populations of Oreochromis niloticus based on their growth performances. Four populations, i.e GIFT-6, Tempe, Local, and GIFT-3 were used in this study. Sixteen 16 cages laid in four earthen ponds in the Cijeruk Research Installation, Bogor, were used as replication. The results showed that there were no significant difference among four populations for biomass, but a significant difference among populations was observed on length parameter (F < 0.01),in which the local population was the best.